2016
DOI: 10.1177/1971400916678223
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings and cognitive functions in a small cohort of myotonic dystrophy type 1: Retrospective analyses

Abstract: Myotonic dystrophy type 1 (DM1) is a progressive multisystemic disease with common cognitive deficits and potential brain involvement in addition to the cardinal muscular and systemic symptoms. Impaired mental function associated with nonspecific pathological findings such as white-matter hyperintense lesions (WMHLs), ventricular enlargement and brain atrophy on brain MRI have been previously reported in DM1 patients. While some studies showed correlation of brain morphological changes with neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“… 42 Bajrami et al . 43 suggest that the WM hyperintense lesions (WMHLs) located at the temporal poles seem to be characteristics of the disease, while others, small and diffuse WMHLs would be similar to the age-related alterations. 43 …”
Section: Discussionmentioning
confidence: 99%
“… 42 Bajrami et al . 43 suggest that the WM hyperintense lesions (WMHLs) located at the temporal poles seem to be characteristics of the disease, while others, small and diffuse WMHLs would be similar to the age-related alterations. 43 …”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this research was to investigate both cognition and a psychological symptomatology association. We opted for a battery containing screening tests (MMSE, for a general cognitive screening; FAB for the assessment of the executive functions) and we decided to go for ENB-2 battery vs. WAIS, because it is validated on the Italian population and it offers the advantage of a shorter assessment time ( 7 , 11 , 12 , 14 , 15 , 18 , 22 , 26 , 27 , 30 , 35 , 39 , 51 , 53 , 56 , 58 , 61 , 62 , 66 69 , 74 , 76 , 78 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown through the used PET, and MRI brain scanning technology, those new neural cells are generated through life as well as new neural pathways [17] [18]. So, old brains are capable of creating measurable changes in brain organization.…”
Section: Discussionmentioning
confidence: 99%
“…Focuses on this issue, researchers are confident that the brain continually adapts and reorganizes. Research about cognitive functions using fMRI found that the neuronal connections in many brain regions appear to be organized differently each time [18] [27].…”
Section: Discussionmentioning
confidence: 99%